Globalization and the Reform of Faculties of Education in Egypt: The Roles of Individual and Organizational, National and International Actors - Ginsburg, Mark; Megahed, Nagwa (Education Policy Analysis Archives, 2011)
In this paper we outline the history of institutionalizing pre-service teacher education in Egypt, and then examine efforts in the mid-1990s to the mid-2000s to reform faculties of education. We document previous criticisms of and proposed changes in teacher preparation programs, but note that concerted reform efforts occurred only after the Egyptian government in the 1990s focused on improving educational quality, including teacher preparation, and the World Bank and USAID also put the issue pre-service teacher education on their agendas – and committed funds for this purpose. We also describe how the proposed reforms of policy and practice (e.g., improving assessments of entrants and graduates, increasing a focus on practice versus theory in coursework, expanding the amount of time devoted to field experiences, and organizing “induction” programs to support and guide new teachers) reflected global teacher education reform discourses characteristic of the 1990s and 2000s. However, rather than treating globalization as a process without real actors, we trace how these ideas were promoted by many Egyptians and non-Egyptians (e.g., faculty of education staff and Ministry of Higher Education personnel, but also World Bank staff, USAID personnel, and members of the two international organization-funded project teams). In examining the planning and implementation of two internationally funded faculty of education reform projects, we explore the interplay between and among local and global actors and identify individual and organizational factors that enabled or constrained these efforts to achieve significant and sustainable improvements in the quality of pre-service teacher education in Egypt.